Dostosowanie Polski do zagranicznej polityki gospodarczej Unii Europejskiej - Rymarczyk, Jerzy (Poland's Adjustment to the European Union, 2005)
The article treats of some aspects of the process of Poland's adjustment to the EU common commercial policy, focusing in particular on the consequences of the adoption of the Union customs duties for Polish economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 107-115